2019
DOI: 10.1177/0886260519847774
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Severity of Maltreatment, Adversity, and Trauma From Child Protective Services Case Record Files

Abstract: Children referred to child protective services (CPS) for allegations of abuse or neglect often have diverse experiences of maltreatment, adversity, and trauma. Severity of these experiences is associated with greater mental health impairment and increased risk of revictimization and other adversities. Although aspects of these experiences are often captured during CPS investigations and stored in case records as narrative documents, much of this information is underutilized in estimating risk and service plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The authors reported that calls with indication of current IPV were more likely to be screened in and subsequently substantiated-likely reflecting a higher level of initial risk assessment. This aligns with work showing that a case history of IPV, even if not the primary purpose of the report, is predictive of repeat allegations of abuse and neglect (Grasso et al, 2019). In the Rebbe et al study, a subset of reports containing IPV co-occurred with physical abuse allegations, more than half co-occurred with neglect, which underscores the unique circumstances in which risk assessment and decision-making must account for IPV.…”
supporting
confidence: 70%
“…The authors reported that calls with indication of current IPV were more likely to be screened in and subsequently substantiated-likely reflecting a higher level of initial risk assessment. This aligns with work showing that a case history of IPV, even if not the primary purpose of the report, is predictive of repeat allegations of abuse and neglect (Grasso et al, 2019). In the Rebbe et al study, a subset of reports containing IPV co-occurred with physical abuse allegations, more than half co-occurred with neglect, which underscores the unique circumstances in which risk assessment and decision-making must account for IPV.…”
supporting
confidence: 70%
“…Because maltreatment often happens in the context of other adversities (Grasso et al, 2019; Radford et al, 2013; Ramos-Olazagasti et al, 2017), we adjust for family socioeconomic status (household classified by information on income/number of household residents as above or below the U.S. federal poverty guidelines); parental psychopathology (any psychological or emotional problem); and parental alcohol/drug abuse problems (yes/no). We also control for study context represented by study site (Puerto Rico/South Bronx) and maternal education (less than high school/at least high school/at least some college education).…”
Section: Methodsmentioning
confidence: 99%
“…More than a third of domestic violence-related arrests involve children who are directly present (Reaves, 2017). Studies that conduct thorough reviews of case records report that the majority of children involved with child protective services have documented IPV exposure in their lifetime (Grasso et al, 2019). Further, more than half of older children and adolescents involved with juvenile justice services have experienced IPV at some point in their lives (Ford et al, 2013b).…”
Section: Intimate Partner Violence-not Just a Partner Problemmentioning
confidence: 99%